A novel adaptive spectrum allocation scheme for multi-channel multi-radio wireless mesh networks. (October 2015) - Ning, Zhaolong; Song, Qingyang; Guo, Lei; Kong, Xiangjie
Abstract: The rapidly developed wireless services and applications have an increasing demand of spectrum resource, which is actually limited. Therefore, how to allocate spectrum resource effectively for network throughput improvement is an urgent issue. Although the utilization of spectrum can be enhanced by link scheduling for spatial reuse, Network Coding (NC) for broadcast transmission, multicast transmission and multi-channel multi-radio techniques, their interactions cannot be ignored. This is because on one hand, the achieved network performance by NC is strongly dependent on the MAC layer, and greedy NC method may in fact reduce network throughput owing to the reduction of spectrum spatial reuse. On the other hand, channel assignment faces more challenges brought by NC and multicast transmission since the broadcast or multicast links are dominated by the link with the worst channel state. In order to utilize the spectrum resource adaptively while not bringing additional constraints, we present a two-phase solution approach. On the first step, we formulate the NC-aware scheduling scheme to an optimization problem, by which the interference-free links are allocated into the same link set and can be activated in the same time slot and channel. Then, we assign different channels to the link sets according to the radio constraints in a heuristic method, which can further increase the utilization of spectrum resource. Finally, simulation results demonstrate that our proposed method can largely increase the utilization of spectrum resource and improve network throughput.